Perception of UITM student toward hysteria: UiTM Campus Samarahan as a scope of study / Siti Azyinie Sabri , Noorfadziela Iswandy & Hazirah Rasdi - Sabri, Siti Azyinie; Iswandy, Noorfadziela; Rasdi, Hazirah (2010)
The topic for our research is about the “Perception of UiTM students toward hysteria which is UiTM Campus Samarahan as a scope of study. The main purpose of this research is to determine what are the contributing factor of the existence of hysteria that is happen in UiTM Campus Samarahan instead of to suggest on how to overcome the phenomena of hysteria and also the effects of hysteria towards student performance. In the chapter 1, it’s about the introduction where by it include the background of the study, problem statement, the objectives of study, scope of study, significant of the study, limitation of our project paper studies.